The Effect of Influencer Marketıng on Trust, Trust Tendency and Consumer Purchase Intentıon: Instagram Example - Yakup Durmaz; Ömer Çavuş; Grzegorz Wilk Jakubowski (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The purpose of this article is to analyze the impact of influencer marketing on trust, trust inclination and consumer purchasing intentions. In addition, this study aims to turn the negative perceptions of influencer marketing of companies into positive and raise awareness accordingly. SPSS 26 and Amos programs were used. In this study; Frequency, percentage, standard deviation, average, factor analysis, correlation and regression analysis were performed on the survey form data, which was easily distributed by sampling method and filled out completely by 411 Instagram users over the age of 18. Instagram influencer marketing has been found to have a positive and positive effect on confidence, confidence trend and consumer purchasing intentions. Not all Instagram users could be reached; The method used limits the general ability of the findings. However, the findings offer preliminary insights into future studies of influencer marketing. Companies will actively interact with customers using various social media platforms and influencers, and thus it is thought that they will succeed in marketing through social media